Knowledge and Perceptions of Chinese Female College Students Towards HIV/AIDS: A Qualitative Analysis - Qiu M; Wu Y (Dove Medical Press, 2022)
Mengying Qiu,1 Yijin Wu2 1School of English Studies, Sichuan International Studies University, Chongqing, 400031, People's Republic of China; 2School of Translation Studies, Qufu Normal University, Rizhao, 276825, People's Republic of ChinaCorrespondence: Yijin Wu, School of Translation Studies, Qufu Normal University, No. 5, Yantai Road, Donggang District, Rizhao, Shandong, 250100, People's Republic of China, Tel/Fax +86 531 88377118, Email wuyijin9972@126.comObjective: This study aims to explore knowledge and perceptions of Chinese female college students towards HIV/AIDS.Design, Method, Participants and Setting: A purposive sampling method was used to recruit participants. Twenty female participants studying at a college located in Chongqing, Southwest China, were involved in the study. Semi-structured interviews were used to collect data. The face-to-face interview data were recorded and analyzed using the method of qualitative inductive content analysis.Results: Five themes were identified from the data of transcribed interviews: HIV transmission routes (sexual transmission; blood transmission; mother-to-child transmission), sources of HIV/AIDS knowledge (education; mass media), AIDS prevention measures (avoiding sexual activity; establishing sense of self-protection; avoiding blood contact), attitudes towards PLWHA (treating all PLWHA equally; showing sympathy for the innocent PLWHA; discriminating against the immoral PLWHA), and suggested solutions to combat AIDS (assistance provided by governments; what health professionals can contribute; mobilization of social power; university intervention).Conclusion: More efforts should be made to strengthen the HIV/AIDS education for female college students of non-medical majors in Southwest China. Accurate knowledge of HIV/AIDS and the right attitudes towards people living with HIV/AIDS (PLWHA) should be the foci of HIV/AIDS education for this population. In order to better cater future sex education in colleges to the requirements of female college students, educators and lawmakers may benefit from gaining a deeper grasp of their perspectives on HIV/AIDS.Keywords: HIV/AIDS, female college students, China, qualitative content analysis